Evaluation of Impacted Lower Third Molars Using Cone Beam Computed Tomography - Soares de Carvalho, José Raimundo; Leite, Josélia da Silva; Oliveira, Rudyard dos Santos (The Journal of Dentists, 2021)
The aim of the study was to define the prevalence of impacted lower third molars using cone beam computed tomography and to classify according to Winter, Pell and Gregory and Maglione. The sample consisted of 250 CBCT exams. The evaluation of the selected images was performed using CS 3D imaging software using axial, cross-section and panoramic reconstruction sections. Data collection was performed by filling out the forms containing the classifications of Winter, Pell and Gregory and Maglione. Data analysis was performed through the distribution of frequencies (absolute and relative) associated with the construction of 95% confidence intervals of proportions. Of the 250 tomography exams analyzed, 113 (45.2%) were male and 137 (54.8%) were female. The positions and differences between the most frequent sides according to the Winter, Pell & Gregory and Maglione classification, respectively, were: Mesioangular - 29.8% (95% CI: 25.8% -33.8%), right side (30.4 %), left side (29.2%); Class II - 31.2% (95% CI: 27.1% -35.3%); position A, right side (30.4%) left side (32.0%); Class 1A - 39.8% (95% CI: 35.5% -44.1%), right side (40.0%), left side (39.6%). Thus, there was a higher prevalence in the mesioangular position according to the Winter classification and, in relation to the Pell and Gregory classification, the class II / A position; while, according to Maglione's classification, the most prevalent position is Class 1A.